The complete mitochondrial genome of Pycanum ochraceum Distant 1893 (Hemiptera: Tessaratomidae). Issue 12 (2nd December 2021) - Wang, Yu-Chen; Li, Gen-Li; Liu, Xin-Yang; He, Qiu-Ju; Yi, Chuan-Hui; Yang, Chen; Zhu, En-Jiao
Abstract: In the present study, the complete mitochondrial genome of Pycanum ochraceum was identified for the first time. The entire genome is 17, 198 bp in length with 73.6% A + T content. It contains 22 transfer RNA genes (tRNAs), 2 ribosomal RNA genes (rRNAs), 13 protein-coding genes (PCGs) and 1 noncoding control region (D-loop). Phylogenetic analysis showed that Tessaratomidae bugs are monophyletic. This study can provide essential DNA molecular data for further phylogenetic and evolutionary analysis for Heteroptera.